PENGARUH KUALITAS PRODUK, HARGA DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN SEPATU DI TOKO D’TRUUF CIMPARUH KOTA PARIAMAN - Erniwati; Ahmad Adnin (Jurnal Point Equilibrium Manajemen dan Akuntansi, 2019)
The objective of the research were to describes : 1) the influence of product quality on buying decision ; 2) the influence of price on buying decision ; 3) the influence of location on buying decision ; 4) the influence of product quality, price and location on buying decision in D’Truuf Store of Cimparuh Pariaman City. Data in the survey using questionnaire and analysis used SPSS Version 16. The sample esed was 100 people and technique using Purposive Sampling.Based on the result of the study can be concluded : 1) product quality take effect positive and significant ; 2) price take effect negative and significant ; 3) location take effect negative and significant ; 4) product quality, price and location take simultaneous effect on buying decision, where is the R value 0,794 and R Square 0,361 or equivalent 63,1% and the rest 36,9% explained by other variables not examined in this study.